Application of Market Basket Analysis to Understand Students' Career Options: A Study on Management under Graduate Students at IU, Mizoram - Bhattacharjee, Mrinmoy; Kalita, Pranjal (Indian Journal of Marketing, 2012)
Judging the career options of the students after their graduation has become a challenging task for professional universities and institutions. Higher education industry in our country has grown at a very significant rate. Institutions are finding it difficult to predict the students' career choices after their graduation. There is a need for extensive research and study to understand the trends of career selection by the students pursuing professional graduate courses and provide them coaching and guidance in that direction. In this context, market basket analysis of data mining is found to be very useful in discovering the trends and patterns of the career selection options after their graduation. This paper is a modest attempt to apply market basket analysis to understand the trends in career selection of the undergraduate management students in IU, Mizoram.